Spatial variation in the functional characteristics of herbivorous fish communities and the resilience of coral reefs. Issue 1 (1st January 2013) - Cheal, Alistair J.; Emslie, Michael; MacNeil, M. Aaron; Miller, Ian; Sweatman, Hugh
Abstract : Many ecosystems face degradation unless factors that underpin their resilience can be effectively managed. In tropical reef ecosystems, grazing by herbivorous fishes can prevent coral–macroalgal phase shifts that commonly signal loss of resilience. However, knowledge of grazing characteristics that most promote resilience is typically experimental, localized, and sparse, which limits broad management applications. Applying sound ecological theory to broad‐scale data may provide an alternative basis for ecosystem management. We explore the idea that resilience is positively related to the diversity within and among functional groups of organisms. Specifically, we infer the relative vulnerability of different subregions of the Great Barrier Reef (GBR) to phase shifts based on functional characteristics of the local herbivorous fish communities. Reef slopes on 92 reefs set in three zones of the continental shelf in eight latitudinal sectors of the GBR were surveyed on multiple occasions between 1995 and 2009. Spatial variation in fish community structure was high and driven primarily by shelf position. Measures of functional diversity, functional redundancy, and abundance were generally higher offshore and lower inshore. Two turbid inshore subregions were considered most vulnerable based on very low measures of herbivore function, and this was supported by the occurrence of phase shifts within one of three subregions. Eleven reefs that resisted phase shifts after major coral mortality included some with very low measures of herbivore function. The fact that phase shifts did not necessarily occur when large herbivores were scarce indicates that other environmental factors compensated to preserve resilience. Estimates of vulnerability based solely on herbivore function may thus prove conservative, but caution is appropriate, since compensatory factors are largely unknown and could be eroded unwittingly by anthropogenic stresses. Our data suggest that managing the threat of phase shifts in coral reef ecosystems successfully will require spatially explicit strategies that consider both the functional characteristics of local herbivore communities and environmental factors that may raise or lower resilience thresholds. A strong positive correlation between water clarity and the species richness and abundance of herbivorous fishes suggests that management of water quality is of generic importance to ensure the ecosystem services of this important group of herbivores.